Characterization of a mesoporous γ-Al2O3 catalyst: Influence of their properties on ethanol conversion. (2018) - García, María Villa; Garbarino, Gabriella; Finocchio, Elisabetta; Busca, Guido; del Hoyo Martínez, Carmen; Escribano, Vicente Sánchez
Abstract: A mesoporous alumina has been synthetized by a hydrothermal method describe by Ĉejka and al. who use as precursor an aluminium isopropoxide and subsequently calcining the precipitate obtained in nitrogen flow at 683 K for 6h. The structural and morphological study evidence that the alumina obtained is a thermal stable γ-Al2 O3 phase up to 1073 K with a specific surface area value of 174 m 2 g -1 . The study of the surface hydroxyl groups in the sample γ-Al2 O3 phase calcined at 1073 K (hereinafter called ALMP1073) reveals the presence of three types of active OH groups absorbing at 3787, 3725 and 3690 cm -1 and that they are significantly acidic, but not enough to protonate pyridine., i.e, they can be considered as Lewis acid. Catalytic test in ethanol dehydration prove that the ALMP1073 sample is active and selective in the dehydration of ethanol to diethylether in the range 523-573 K, as well as in the dehydration of ethanol to ethylene in the range 623-723 K These data are consistent with those obtained by infrared spectroscopy. The ethoxy groups formed on the surface of γ-Al2 O3 are proposed as intermediate species in the ethanol dehydration reaction for both diethylether and ethylene formation.